Surgical management of Benign Prostatic Hyperplasia: Transvesical prostatectomy versus Transurethral resection of prostate with a volume range of 70–100 gram (Journal of Academic Research, 2025)
Objectives: This study aims to compare the short-term outcomes and complications of transvesical prostatectomy versus monopolar transurethral resection of the prostate between 70 and 100 grams.Methods and material: This is a retrospective descriptive study conducted from April 2017 to April 2021. A total of 59 patients were admitted and underwent transvesical prostatectomy (TVP) and transurethral resection of the prostate (TURP) at Misrata Medical Center (department of urology). Patients with prostatic volume between 70-100 g were included in this study, while patients with prostatic volume greater than 100 g or less than 70 g were excluded. Types of surgery (TVP and TURP), patient age, size of the prostate gland, duration of surgery (mins), blood transfusion, clot retention, length of catheterization (days), hospital stay (days), post-operative infection, incontinence, reoperation, bladder neck stenosis, and urethral stricture were analyzed.
Keywords: Transvesical; prostatectomy; monopolar; transurethral; resection